ELICITATION OF TRIGONELLINE, A HYPOGLYCEMIC AGENT IN FENUGREEK SPROUTS BY CALCIUM AND NITRIC OXIDE PRIMING - GUPTA SK; NANDA AK; GHOSH R; MANDAL P (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This work was performed to evaluate the effect of priming with exogenous sources of calcium ion and nitric oxide on the antidiabetic activity and the alkaloid contents of fenugreek sprouts along with isolation and identification of trigonelline, a bioactive alkaloid responsible for hypoglycemic property of fenugreek. Methods: The fenugreek seeds were pre-treated with calcium chloride (CC), lanthanum chloride (LC) a calcium channel blocker; ethylene glycol-bis (2-aminoethylether) -N, N, NÂ´, N tetra acetic acid (EG) a calcium chelator; sodium nitroprusside (SNP) and 2-(4-carboxyphenyl) -4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (CP) a nitric oxide scavenger and germinated for 72 hrs. The sprout extracts were evaluated for their in vitro antidiabetic potential by Î±-amylase and Î±-glucosidase inhibition along with their trigonelline content. Trigonelline was isolated from fenugreek sprouts and identified by Infrared analysis and nuclear magnetic resonance (NMR) spectroscopy. Results: The results revealed that sprouts pre-treated with CC and SNP exhibited enhanced antidiabetic potential as well as alkaloid content over control; on the other hand, their action was reversed by their antagonists, EG, LC, and CP. The sprouts pre-treated with 2mM CC showed the best elicitation of alkaloid content and antidiabetic activity followed by SNP-20 mM. Conclusions: The study suggests probable involvement of the signaling molecules, calcium ion, and nitric oxide in pathways associated with biosynthesis of bioactive compounds responsible for hypoglycemic activity of fenugreek sprouts one of which being trigonelline. Â Â